Pengaruh Pengalaman Belanja Online Produk Fashion terhadap Kepuasan dan Niat Beli Ulang Pelanggan Zalora serta Berrybenka - Bob Foster (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2017)
Internet is not only used to communicate, but also as electronic commerce media or better known as ecommerce (electronic commerce). In e-commerce, the most purchased goods online are fashion products.Therefore, researchers want to know whether the online shopping experience affects customer satisfaction aswell as intention to repurchase. Data collection techniques in this study using questionnaires and other literarysources of other books. After doing the data processing was the result of questionnaire data declared valid andreliable. Furthermore, to know the influence of each variable performed data processing using AMOS 24 byforming SEM model and Path Analysis. From test result of Fit Structural Model Model known all indicator canbe stated fit. And then from the Regression Weight Structural Model test results obtained that the onlineshopping experience affects customer satisfaction, then the online shopping experience affects the intention torepurchase, and satisfaction affects the intention to repurchase.